A 3.15-mW +16.0-dBm IIP3 22-dB CG Inductively Source Degenerated Balun-LNA Mixer With Integrated Transformer-Based Gate Inductor and IM2 Injection Technique - Vitee, Nandini; Ramiah, Harikrishnan; Mak, Pui-In; Yin, Jun; Martins, Rui Paulo (Institute of Electrical and Electronics Engineers, 2020)
This article proposes two linearization techniques in improving the third-order input intercept point (IIP3) of a balun-low-noise amplifier (LNA) mixer. First, the intrinsic third-order intermodulation (IM3) product of the inductively source degenerated (ISD) transconductor from the second-order derivative transconductance component ({g}''m) is reduced by tailoring toward the optimum biasing point at the moderate-inversion region. Second, the generated IM3 current by the first-order derivative transconductance ({g}'m) due to the interaction with the feedback component in the ISD transconductor is attenuated by second-harmonic injection via the bulk of the ISD transconductor. Furthermore, a transformer-based gate inductor and a transformer-based balun are applied to improve the input impedance matching and produce a balanced differential input signal. Measured results in 0.13- μ m CMOS show a high IIP3 of +16 dBm and a conversion gain (CG) of 22 dB at 2.4 GHz. The double-sideband (DSB) noise figure (NF) is 7.2 dB, and the power consumption is 3.15 mW at 1.2 V. © 1993-2012 IEEE.